Pengaruh Loan to Deposit dan Non Performing Loan terhadap Return On Assets Pada Bank Umum kelompok BUKU 4 - Kinanti Nur' Anisa; Radia Purbayati; Dadang Hermawan (Indonesian Journal of Economics and Management, 2021)
The aims of this research to examine the effect of Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) on Return On Assetss (ROA) in the Commercial Bank category BUKU 4 period 2016-2020. The population are commercial banks that already listed on the Indonesia Stock Exchange (IDX). The method of sampling used purposive sampling was obtained from 7 Commercial Bank category BUKU 4. The analysis technique used is regression analysis with a data panel used by Eviews 9 Software. The selected panel data regression model is Random Effect Model (REM). The result showed that Loan to Deposit Ratio (LDR) partially had no signifikan effect on Return On Assetss (ROA) and Non Performing Loan (NPL) partially had a negative effect and signifikan on Return On Assets (ROA). While Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) simultaneously had a signifikan effect on Return On Assets (ROA).